Improved Indium-Free Transparent ZnO/Metal/ZnO Electrode through a Statistical Experimental Design Method - Pang Shiu Chen; Cheng-Hsiung Peng; Yu-Wei Chang; Tzu Wei Lin; S. W. Lee (Advances in Materials Science and Engineering)
ZnO/Ag/ZnO (ZAZ) and ZnO/Cu/ZnO (ZCZ) were prepared. The dependence of crystalline, electrical, and optical properties for the multilayer on the postdeposition annealing (PDA) was studied. After PDA of 300°C for 20 min, the diffusion of Cu in ZnO occurs; this result is responsible for the increasing resistance of the annealed ZCZ. Ag with a thickness of 10 nm was deposited upon ZnO. The interface of ZnO and Ag is clearly revealed by high resolution transmission electron microscopy. The crystalline of ZnO and Ag films in the ZAZ with a sheet resistance (Rs) down to 4.17 Ω/sq. The ZAZ layer shows a better thermal stability (up to 400°C) than that of the ZCZ ones. The PDA degraded slightly the optical transmittance and increases the conductivity of ZAZ layer. The figure of merit (FOM) is applied to analysis of the ZAZ layer. The PDA can enhance the FOM of the ZAZ with Ag thickness >8 nm. The resulting Rs and the transmittance ZAZ layers were analyzed by the Taguchi method to obtain the appropriate parameters. The optimized ZAZ has been verified with a Rs of 2.3 Ω/sq, a high transmittance (71%), and the optimal FOM of 1.41 × 10−2 Ω−1.